Dye compound and optical material

By introducing large sterically hindered aromatic rings and hydrophobic structures into pigment compounds and forming covalent bonds with material macromolecules, the problem of insufficient dyeing stability of optical materials is solved, and high stability and safety of pigments are achieved.

CN119798165APending Publication Date: 2025-04-11HUNAN LANGSHENG MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411952213.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The dyeing stability of optical materials is insufficient, which leads to easy disengagement of pigments during use, affecting the wear safety and use effect of the device.

Method used

A pigment compound was developed, in which large sterically hindered aromatic rings were introduced as side chains to enhance the conformational change speed and color stability of the color development structure. At the same time, by introducing hydrophobic structures and active reaction points, the pigments form covalent bonds with the material macromolecules to prevent the freeing and migration of pigments.

Benefits of technology

It improves the dyeing stability of pigments, reduces the dissolution and migration of pigments during use, and enhances the color retention ability and safety of optical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798165A_ABST
    Figure CN119798165A_ABST
Patent Text Reader

Abstract

The invention discloses a pigment compound and an optical material, and belongs to the technical field of compounds, the pigment compound has a structure as shown in the following formula (I): # imgabs0 #, A is a hydrogen atom or methyl; r1 is a hydrogen atom, a halogen atom, a cyano group, an aryl group, an alkyl group with 1-6 carbon atoms or an alkoxy group with 1-6 carbon atoms, and n is equal to 1, 2, 3, 4 or 5; k = 0, 1, 2, 3, 4, 5 or 6; r2 is a hydrogen atom, a halogen atom, a cyano group, a nitro group, a sulfo group, an alkyl group with 1-6 carbon atoms or an alkoxy group with 1-6 carbon atoms, and m is equal to 1, 2, 3 or 4; b is a cyclic conjugated group, a derivative of the cyclic conjugated group, or a substituted derivative of the cyclic conjugated group. The pigment compound provided by the invention can be subjected to a copolymerization reaction with an olefin monomer in an optical material, so that the technical effect of improving the dyeing stability of the optical material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of compound technology, and in particular to a pigment compound and an optical material. Background Art

[0002] Optical materials, especially optometry medical devices, have high requirements for pigments. Pigments are widely needed in both corneal contact lenses and intraocular lenses. Developing high-quality new pigments is one of the important ways to improve device performance.

[0003] In terms of corneal contact lenses, such as contact lenses, cosmetic lenses, OK lenses, etc., common dyeing methods have relatively large disadvantages in terms of dyeing stability. For example, when a layer of color is plated on the surface of the lens, it is difficult to avoid the removal of the pigment, which affects the health of the eyes; for another example, when a non-reactive dye is mixed with a chemical raw material and solidified to obtain a colored material, corneal contact lenses often need to be disinfected and cleaned with a care solution on a daily basis. The pigment contained in the lens will dissolve during use, which causes problems with the safety of wearing the lens and the effect of use. Although the use of a "sandwich" interlayer to seal the pigment in the middle layer improves the stability of the pigment, this process is not convenient to operate, and there is also the problem of insufficient tightness of the "sealed" pigment. Summary of the invention

[0004] The main purpose of the present application is to provide a pigment compound and an optical material, aiming to solve the technical problem of insufficient dyeing stability of optical materials.

[0005] To achieve the above object, the present application provides a pigment compound having a structure shown in the following formula (I):

[0006]

[0007] Wherein, A is a hydrogen atom or a methyl group;

[0008] R 1 is a hydrogen atom, a halogen atom, a cyano group, an aryl group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and n=1, 2, 3, 4 or 5;

[0009] k = 0, 1, 2, 3, 4, 5 or 6;

[0010] R 2 is a hydrogen atom, a halogen atom, a cyano group, a nitro group, a sulfonic acid group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and m=1, 2, 3 or 4;

[0011] B is a cyclic conjugated group, a derivative of a cyclic conjugated group, or a substituted derivative of a cyclic conjugated group.

[0012] In the technical solution of the present application, a large sterically hindered aromatic ring is introduced into the pigment compound molecule to provide a larger activity space for the side chain, so that the conformation of the color-developing structure can change rapidly and the color is stable quickly; a large proportion of hydrophobic structures such as aromatic rings, hydrocarbon chains, and ester bonds can enhance the miscibility with strongly hydrophobic monomer raw materials and enhance the affinity with strongly hydrophobic copolymer materials; and the pigment has a variety of adjustable functional group structures, and different color appearances can be expressed by changing the group combination in the structure. In addition, the introduction of active reaction points allows the formation of covalent bonds between the chromophore structure of the pigment and the material macromolecule, solving the problem of free pigments migrating from the inside of the material, and improving the dyeing stability.

[0013] In some embodiments of the present application, the B group has a structure as shown in the following formula b1:

[0014]

[0015] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0016] R 4 It is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

[0017] In some embodiments of the present application, it has a structure shown in the following formula A1, A2 or A6:

[0018]

[0019] In some embodiments of the present application, the B group has a structure as shown in the following formula b2:

[0020]

[0021] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0022] R 4 It is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

[0023] In some embodiments of the present application, it has a structure shown in the following formula A4:

[0024]

[0025] In some embodiments of the present application, the B group has a structure as shown in the following formula b3:

[0026]

[0027] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0028] i=1, 2, 3, 4 or 5.

[0029] In some embodiments of the present application, it has a structure shown in the following formula A3 or A7:

[0030]

[0031] In some embodiments of the present application, the B group has a structure as shown in the following formula b4:

[0032]

[0033] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0034] R 4is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0035] i = 1, 2 or 3;

[0036] j=1, 2, 3 or 4.

[0037] In some embodiments of the present application, it has a structure shown in the following formula A5:

[0038]

[0039] In addition, to achieve the above purpose, the present application also provides an optical material, including the pigment compound as described above, wherein the pigment compound and the olefin monomer form a covalent bond through copolymerization. The introduction of active sites in the pigment compound can copolymerize with the olefin monomer, and the covalent bond formed is not easily destroyed, which can enhance the stability of dyeing. The pigment compound of the embodiment of the present application is applied to optometry medical devices, which has good practicality. In terms of corneal contact lens materials, various color appearance requirements can be provided, and its strong hydrophobic characteristics are suitable for application in highly oxygen permeable corneal contact lenses containing highly hydrophobic high fluorine silicon components. In terms of intraocular lens materials, a blue light shielding effect of a specific band can be provided to protect the retina from damage, and an optional specific structure provides specific absorption of short-wavelength blue light. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions in the embodiments of the present drawings or related technologies, the drawings required for use in the embodiments or related technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0041] Figure 1 This is a graph showing the absorption spectra of the pigments A1 to A7 in the range of 300 to 800 nm in the examples of the present application;

[0042] Figure 2 Appearance diagram of corneal contact lens sheet material prepared in Examples D1 to D10 of the present application;

[0043] Figure 3 Spectral transmittance test charts of intraocular lens materials prepared for Examples E1 to E8 of the present application;

[0044] Figure 4This is an appearance diagram of the pigment migrating to the mold after the materials D1 to D10 of the present application are cured;

[0045] Figure 5 This is the spectral absorption diagram of the immersion eluent of corneal contact lens materials D2, D3, D5, D8, D9, and D10 in the embodiment of the present application;

[0046] Figure 6 This is a spectral transmittance curve of the intraocular lens material E4 of the present application example before and after leaching and elution;

[0047] Figure 7 This is a spectral transmittance curve of the corneal contact lens material D5 of the present application example before and after leaching and elution;

[0048] Figure 8 This is a spectral transmittance curve of the corneal contact lens material D8 before and after leaching and elution in the embodiment of the present application;

[0049] Fig. 9 This is a spectral transmittance curve of the corneal contact lens material D9 of the embodiment of the present application before and after leaching and elution. DETAILED DESCRIPTION

[0050] Hereinafter, the pigment compound and the embodiment of the optical material of the present application are specifically disclosed with reference to the accompanying drawings in detail. However, there will be a situation where unnecessary detailed description is omitted. For example, there is a situation where the detailed description of well-known matters and the repeated description of the actual same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the accompanying drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recorded in the claims.

[0051] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the technical solution of the present application is further described below in conjunction with the accompanying drawings and embodiments. However, the present application is not limited to the listed embodiments, and should also include any other known changes within the scope of the rights claimed in the present application.

[0052] The present application provides a pigment compound, which has a structure shown in the following formula (I):

[0053]

[0054] Wherein, A is a hydrogen atom or a methyl group;

[0055] R 1 is a hydrogen atom, a halogen atom, a cyano group, an aryl group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and n=1, 2, 3, 4 or 5;

[0056] k = 0, 1, 2, 3, 4, 5 or 6;

[0057] R 2 is a hydrogen atom, a halogen atom, a cyano group, a nitro group, a sulfonic acid group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and m=1, 2, 3 or 4;

[0058] B is a cyclic conjugated group, a derivative of a cyclic conjugated group, or a substituted derivative of a cyclic conjugated group.

[0059] Understandably, R 1 and R 2 The halogen atom in may be fluorine, chlorine, bromine or iodine. The cyclic conjugated group refers to a cyclic structural group that can form a conjugated electron system.

[0060] In the technical solution of the present application, a large sterically hindered aromatic ring is introduced into the pigment compound molecule to provide a larger activity space for the side chain, so that the conformation of the color-developing structure can change rapidly and the color is stable quickly; a large proportion of hydrophobic structures such as aromatic rings, hydrocarbon chains, and ester bonds can enhance the miscibility with strongly hydrophobic monomer raw materials and enhance the affinity with strongly hydrophobic copolymer materials; and the pigment has a variety of adjustable functional group structures, and different color appearances can be expressed by changing the group combination in the structure. In addition, the introduction of active reaction points allows the formation of covalent bonds between the chromophore structure of the pigment and the material macromolecule, solving the problem of free pigments migrating from the inside of the material, and improving the dyeing stability.

[0061] In some embodiments of the present application, the B group has a structure as shown in the following formula b1:

[0062]

[0063] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0064] R 4 It is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

[0065] In some embodiments of the present application, the pigment compound has a structure shown in the following formula A1, A2 or A6:

[0066]

[0067] In some embodiments of the present application, the B group has a structure as shown in the following formula b2:

[0068]

[0069] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0070] R 4 It is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

[0071] In some embodiments of the present application, the pigment compound has a structure as shown in the following formula A4:

[0072]

[0073] In some embodiments of the present application, the B group has a structure as shown in the following formula b3:

[0074]

[0075] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0076] i=1, 2, 3, 4 or 5.

[0077] In some embodiments of the present application, the pigment compound has a structure shown in the following formula A3 or A7:

[0078]

[0079] In some embodiments of the present application, the B group has a structure as shown in the following formula b4:

[0080]

[0081] Among them, R 3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0082] R 4 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group;

[0083] i = 1, 2 or 3;

[0084] j=1, 2, 3 or 4.

[0085] In some embodiments of the present application, the pigment compound has a structure shown in the following formula A5:

[0086]

[0087] The present application also provides an optical material, including the pigment compound as described in the above embodiment, the pigment compound and the olefin monomer form a covalent bond through copolymerization. The introduction of active sites in the pigment compound can cause copolymerization with the olefin monomer, and the covalent bond formed is not easy to be destroyed, which can enhance the stability of dyeing. The pigment compound of the embodiment of the present application is applied to optometry medical devices, which has good practicality. In terms of corneal contact lens materials, a variety of color appearance requirements can be provided, and its strong hydrophobic characteristics are suitable for application in highly oxygen-permeable corneal contact lenses containing highly hydrophobic high-fluorine silicon components. In terms of intraocular lens materials, a blue light shielding effect of a specific band can be provided to protect the retina from damage, and an optional specific structure provides specific absorption of short-wavelength blue light.

[0088] In some embodiments of the present application, several pigment compounds with specific functional structures can be prepared by organic synthesis. Then, the prepared pigment compounds can be applied to the preparation of optical materials and their actual effects can be tested.

[0089] In some embodiments of the present application, the synthesis route of the pigment compound having the structure of formula (I) is as follows.

[0090]

[0091] Using nitro-substituted phenylalkyl carboxylic acids and their structural analogs as raw materials, an aromatic ring structure is introduced by addition to obtain B1, which is then esterified to obtain B2. B2 is then reduced to obtain B3, and then coupled to obtain B4, wherein B1, B2, and B3 are intermediate general formulas, and B4 is the general formula of the final product.

[0092] 1. Preparation Example

[0093] Example 1

[0094] Synthesis of Compound A1: Intermediate C3 was synthesized according to the following synthetic route, and then compound A1 was synthesized from intermediate C3.

[0095]

[0096] First, the intermediate C3 is synthesized, which includes the following three steps:

[0097] The first step is to synthesize C1 from p-nitrobenzoic acid. In a single-necked flask, accurately weigh p-nitrobenzoic acid (2.00 g, 12.0 mmol), styrene oxide (1.44 g, 12.0 mmol), and tetrabutylammonium bromide (0.1 g), then add 40 mL of DMF, put in a magnetic stirrer, set the temperature to 80 ° C, react overnight, raise the temperature to 100 ° C the next day, and continue to react for 2 hours. Stop the reaction, wait for cooling, and remove the solvent by rotary evaporation. The residue is dissolved in ethyl acetate and washed twice with saturated sodium bicarbonate and deionized water. Collect the organic phase and dry it with anhydrous magnesium sulfate overnight. Filter the filtrate by suction, and the filtrate is rotary evaporated to dryness to obtain a viscous substance. It is purified by column chromatography (ethyl acetate / petroleum ether = 1 / 3) to obtain 0.70 g, 2.4 mmol of compound C1 as a white solid with a yield of 16.3%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.33 (d, J=8.9Hz, 2H), 8.25 (d, J=8.9Hz, 2H), 7.49 (d, J=7.3Hz, 2H), 7.44 (t, J=7.5Hz, 2H), 7.38 (t, J=7.3Hz, 1H), 5.21-5.13 (m, 1H), 4.59 (dd, J=11.6, 3.6Hz, 1H), 4.53 (dd, J=11.6, 8.0Hz, 1H), 2.40 (d, J=3.4Hz, 1H).

[0098] In the second step, C3 is synthesized from C2. In a single-mouth flask, the product C1 (0.70 g), triethylamine (0.37 g), and DMAP (0.05 g) of the previous step are added thereto, and then 20 mL of tetrahydrofuran is added, and a magnetic bar is placed, and stirred under an ice bath. Then methacryloyl chloride (0.38 g) is weighed, diluted with an appropriate amount of tetrahydrofuran, and slowly added dropwise into the above system in a constant pressure dropping funnel. After the addition is completed, continue to stir for 2 hours, then transfer it to room temperature and continue to stir for 12 hours. Remove the filter residue by suction filtration, collect the filtrate, and remove the solvent by rotary evaporation. The residue is dissolved in ethyl acetate, and washed three times with saturated sodium bicarbonate and deionized water respectively. The organic phase is collected by a separatory funnel, and the organic phase is dried with anhydrous magnesium sulfate for 4 hours, and the filtrate is collected by filtration. The filtrate was subjected to rotary evaporation to remove the solvent, and the crude product was collected and purified by column chromatography (ethyl acetate / petroleum ether=1 / 5) to obtain 0.20 g of compound C2 as a light yellow viscous body with a yield of 23.1%. The 1HNMR test was performed to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.33-8.29 (m, 2H), 8.18 (d, J=8.9Hz, 2H), 7.48 (d, J=7.1Hz, 2H), 7.43 (t, J=7.3Hz, 2H), 7.41-7.36 (m, 1H), 6.32-6.26 (m, 1H), 6.23 (s, 1H), 5.65 (dd, J=6.7, 5.2Hz, 1H), 4.74-4.62 (m, 2H), 1.98 (s, 3H).

[0099] The third step is to synthesize C3 from C2. In a single-necked flask, accurately weigh C2 (0.15g) and anhydrous stannous chloride (0.41g), dissolve in 7mL of anhydrous ethanol, drop 0.15mL of concentrated hydrochloric acid, add a small amount of cuprous chloride to inhibit polymerization, put in a magnetic bar for stirring, and react at 65°C for 1.5 hours. After the reaction is completed, the solvent is removed by rotary evaporation, deionized water is added, the pH is adjusted to neutral, and then dichloromethane is added to extract to obtain an organic phase, which is washed with water twice. The organic phase is dried with anhydrous magnesium sulfate, and after drying, the filtrate is collected by filtration, and the solvent is removed by rotary evaporation. The product C3 is directly used for the next reaction.

[0100] Compound A1 was synthesized from C3. In a single-mouth flask, the product C3 (0.14 g) of the previous step was added, 20 mL of acetone was added, 2 mL of deionized water was added dropwise, 0.25 mL of concentrated hydrochloric acid was added dropwise, and a magnetic stirrer was placed to dissolve it. The mixture was placed at -2°C, sodium nitrite (0.03 g) was weighed and prepared into 15 mL of aqueous solution, and slowly added dropwise to the above solution. After the addition was completed, stirring was continued for 2 hours to obtain a diazonium salt solution, which was recorded as solution 1. In another single-mouth flask, 3-methyl-1-phenyl-5-pyrazolone (0.07 g) was accurately weighed, 4 mL of deionized water, 0.02 g of sodium hydroxide, and 1 mL of acetone were added. The mixture was placed at -5°C, and a magnetic stirrer was placed to completely dissolve it, which was recorded as solution 2. The obtained solution 1 was transferred to a constant pressure dropping funnel and slowly added dropwise to solution 2. After the addition was completed, stirring was continued for 3 hours, and the color of the solution gradually became darker. After the reaction was completed, acetone was removed by rotary evaporation, an appropriate amount of water was added, and the mixture was extracted three times with dichloromethane. The organic phase was collected and dichloromethane was removed by rotary evaporation. The remaining material was purified by column chromatography (ethyl acetate / petroleum ether = 1 / 5) to obtain compound A1 (0.05 g, 0.10 mmol) as a red solid with a yield of 23.5%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.08 (t, J=9.1Hz, 2H), 7.97 (d, J=7.8Hz, 2H), 7.52-7.40 (m, 8H), 7.38 (t, J=7.3Hz, 1H), 7.25 (t, J=7.4Hz, 1H), 6.27 (dd, J=8.0, 3.8Hz, 1H), 6.24 (s, 1H), 5.67-5.61 (m, 1H), 4.76-4.58 (m, 2H), 2.40 (s, 3H), 1.99 (s, 3H).

[0101] Example 2

[0102] Synthesis of Compound A2. First, C3 was synthesized according to the steps in Example 1. Compound A2 was then synthesized from the obtained C3 (0.14 g), and the operation was consistent with that in Example 1, except that 3-methyl-1-phenyl-5-pyrazolone (0.07 g) in Example 1 was replaced with 1,3-dimethyl-5-pyrazolone (0.05 g). Finally, Compound A2 (0.08 g, 0.18 mmol) was purified by column chromatography as a yellow solid with a yield of 42.4%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.05 (d, J=8.8Hz, 2H), 7.48 (d, J=7.2Hz, 2H), 7.43 (dd, J=16.2,8.2Hz, 4H), 7.37 (t, J=7.3Hz, 1H), 6.26 (dd, J=8.0,3.9Hz, 1H), 6.23 (s, 1H), 5.66-5.61 (m, 1H), 4.63 (ddd, J=15.7,11.8,6.0Hz, 2H), 3.43 (s, 3H), 2.29 (s, 3H), 1.99 (s, 3H).

[0103] Example 3

[0104] Synthesis of Compound A3: First, the intermediate C5 was synthesized according to the following synthetic route, and then the compound A3 was synthesized from the intermediate C5.

[0105]

[0106] First, the intermediate C5 is synthesized, which includes the first to third steps.

[0107] In the first step, C1 is synthesized from p-nitrobenzoic acid, and the operation steps are consistent with those in Example 1.

[0108] The second step is to synthesize C4 from C1. In a single-necked flask, accurately weigh C1 (3.05g), triethylamine (2.20g), and DMAP (0.20g), add them, then add 20mL of tetrahydrofuran, put in a magnetic bar, and stir in an ice bath. Then weigh acryloyl chloride (1.92g), dilute it with an appropriate amount of tetrahydrofuran, and slowly add it dropwise into the above system in a constant pressure dropping funnel. After the addition is completed, continue to stir for 2 hours, then transfer it to room temperature and continue stirring for 12 hours. Remove the filter residue by suction filtration, collect the filtrate, remove the solvent by rotary evaporation, dissolve the residue in ethyl acetate, wash it three times with saturated sodium bicarbonate and deionized water respectively, collect the organic phase with a separatory funnel, dry the organic phase with anhydrous magnesium sulfate for 4 hours, and collect the filtrate by filtration. The filtrate was evaporated to remove the solvent, and the crude product was collected and purified by column chromatography (ethyl acetate / petroleum ether=1 / 5) to obtain 0.87 g of compound C4 as a light yellow viscous substance. The yield was 24.1%. 1H NMR test was performed to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.31 (d, J = 8.9 Hz, 2H), 8.18 (d, J = 8.9 Hz, 2H), 7.48 (d, J = 7.2 Hz, 2H), 7.43 (d, J = 7.5 Hz, 2H), 7.41-7.39 (m, 1H), 6.52-6.46 (m, 1H), 6.36-6.27 (m, 1H), 6.26-6.18 (m, 1H), 5.92 (dd, J = 10.5, 1.1 Hz, 1H), 4.71-4.64 (m, 2H).

[0109] The third step is to synthesize C5 from C4. In a single-necked flask, accurately weigh C4 (0.24g) and anhydrous stannous chloride (0.68g), dissolve in 7mL of anhydrous ethanol, drop 0.25mL of concentrated hydrochloric acid, add a small amount of cuprous chloride to inhibit polymerization, put in a magnetic bar for stirring, and react at 65°C for 1.5 hours. After the reaction is completed, the solvent is removed by rotary evaporation, deionized water is added, the pH is adjusted to neutral, and then dichloromethane is added to extract to obtain an organic phase, which is washed with water twice. The organic phase is dried with anhydrous magnesium sulfate, and after drying, the filtrate is collected by filtration, and the solvent is removed by rotary evaporation to obtain the product C5 (0.20g), which is directly used in the next step reaction.

[0110] Compound A3 was synthesized from C5. In a single-necked flask, C5 (0.20 g) was weighed, 5 mL of acetone was added, 1 mL of deionized water was added dropwise, 0.38 mL of concentrated hydrochloric acid was added dropwise, and a magnetic stirrer was placed to dissolve it. The mixture was placed at -2°C, sodium nitrite (0.045 g) was weighed and prepared into 5 mL of aqueous solution, and slowly added dropwise to the above solution. After the addition was completed, stirring was continued for 2 hours to obtain a diazonium salt solution, which was recorded as solution 1. In another single-necked flask, phenol (0.18 g) was accurately weighed, 15 mL of deionized water and 0.078 g of sodium hydroxide were added, the mixture was placed at -5°C, and a magnetic stirrer was placed to completely dissolve it, which was recorded as solution 2. The obtained solution 1 was transferred to a constant pressure dropping funnel, and slowly added dropwise to solution 2. After the addition was completed, stirring was continued for 3 hours, and the color of the solution gradually became darker. After the reaction was completed, acetone was removed by rotary evaporation, an appropriate amount of water was added, and the mixture was extracted three times with dichloromethane. The organic phase was collected and dichloromethane was removed by rotary evaporation. The remaining material was purified by column chromatography (ethyl acetate / petroleum ether = 1 / 3) to obtain compound A3 (0.05 g, 0.12 mmol) as a red solid with a yield of 18.5%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600 MHz, CDCl3) δ8.15 (d, J=8.5 Hz, 2H), 7.92 (dt, J=9.6, 5.8 Hz, 4H), 7.50 (d, J=7.3 Hz, 2H), 7.43 (t, J=7.4 Hz, 2H), 7.41-7.38 (m, 1H), 6.98 (d, J=8.8 Hz, 2H), 6.51 (dd, J=17.3, 1.1 Hz, 1H), 6.33 (dd, J=8.0, 3.9 Hz, 1H), 6.24 (dd, J=17.3, 10.5 Hz, 1H), 5.91 (dd, J=10.5, 1.1 Hz, 1H), 4.72-4.60 (m, 2H).

[0111] Example 4

[0112] Synthesis of Compound A4. First, C5 was synthesized, and then Compound A4 was synthesized from C5. The synthesis operation was the same as that in Example 3. The difference from Example 3 was that the raw material for preparing Solution 2 was replaced with 1,3-dimethyl-5-hydroxypyrazole (0.07 g), and 15 mL of deionized water and 0.03 g of sodium hydroxide were added. Compound A4 (0.12 g, 0.28 mmol) was obtained as a yellow solid with a yield of 45.5%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ13.42(s,1H),8.14(d,J=8.8Hz,1H),8.05(d,J=8.8Hz,2H),7.47(t,J=5.4Hz,2H),7.44-7.41(m,2H),7.38(t,J=5.6Hz,1H),6.50(dd,J=17.3,1.2Hz,1H),6.32-6.27(m,1H),6.26-6.18(m,1H),5.90(dd,J=10.5,1.2Hz,1H),4.67-4.58(m,2H),3.42(s,3H),2.29(s,3H).

[0113] Example 5

[0114] Synthesis of Compound A5: First, the intermediate C8 was synthesized according to the following synthetic route, and then the compound A5 was synthesized from the intermediate C8.

[0115]

[0116] First, the intermediate C8 is synthesized. The synthesis of C8 includes the following three steps:

[0117] The first step is to synthesize C6 from m-nitrophenylpropionic acid. In a single-necked flask, accurately weigh m-nitrophenylpropionic acid (5.00 g, 25.6 mmol), styrene oxide (3.08 g, 25.6 mmol), and tetrabutylammonium bromide (0.25 g), then add 80 mL of DMF, put in a magnetic stirrer, set the temperature to 80 ° C, react overnight, raise the temperature to 100 ° C the next day, and continue to react for 2 hours. Stop the reaction, wait for cooling, and remove the solvent by rotary evaporation. The residue is dissolved in ethyl acetate and washed twice with saturated sodium bicarbonate and deionized water respectively. Collect the organic phase and dry it with anhydrous magnesium sulfate overnight. Filter the filtrate, and rotary evaporate the filtrate to dryness to obtain a liquid substance. It is purified by column chromatography (ethyl acetate / petroleum ether = 1 / 3) to obtain 2.54 g, 8.1 mmol of compound C6, which is a colorless liquid with a yield of 31.6%. 1H NMR test was performed on it to confirm its chemical structure, 1H NMR (600MHz, CDCl3) δ8.16–8.07 (m, 2H), 7.56 (d, J=7.5Hz, 1H), 7.48 (dd, J=8.5, 7.7Hz, 1H), 7.39 (dd, J=5.7, 4.9Hz, 4H), 7.36–7.33 (m, 1H), 4.96 (d, J=6.2Hz, 1H), 4.37–4.28 (m, 1H), 4.22 (dd, J=11.6, 8.3Hz, 1H), 3.09 (t, J=7.5Hz, 2H), 2.83–2.71 (m, 2H), 2.40 (d, J=19.5Hz, 1H).

[0118] The second step is to synthesize C7 from C6. In a single-necked flask, accurately weigh C6 (2.54 g, 8.1 mmol), triethylamine (1.23 g, 12.2 mmol), and DMAP (0.2 g), add them, then add 50 mL of tetrahydrofuran, put in a magnetic bar, and stir in an ice bath. Then weigh acryloyl chloride (1.10 g, 12.2 mmol), dilute with an appropriate amount of tetrahydrofuran, and slowly add it dropwise into the above system in a constant pressure dropping funnel. After the addition is completed, continue to stir for 2 hours, then transfer it to room temperature and continue to stir overnight. Remove the filter residue by suction filtration, collect the filtrate, remove the solvent by rotary evaporation, dissolve the residue in ethyl acetate, wash it three times with saturated sodium bicarbonate and deionized water respectively, collect the organic phase with a separatory funnel, dry the organic phase with anhydrous magnesium sulfate for 4 hours, and collect the filtrate by filtration. The filtrate was evaporated to remove the solvent, and the crude product was collected and purified by column chromatography (ethyl acetate / petroleum ether=1 / 5) to obtain 1.06 g, 2.87 mmol of compound C7 as a colorless viscous liquid. The yield was 35.4%. It was tested by 1H NMR, 1H NMR (600MHz, CDCl3) δ8.12–8.05 (m, 2H), 7.53 (t, J=6.5Hz, 1H), 7.46 (dd, J=14.2, 6.4Hz, 1H), 7.40–7.34 (m, 5H), 6.47 (dd, J=17.3, 1.2Hz, 1H), 6.19 (dd, J=17.3, 10.5Hz, 1H), 6.14–6.09 (m, 1H), 5.90 (dd, J=10.5, 1.2Hz, 1H), 4.46–4.34 (m, 2H), 3.07 (dt, J=18.8, 7.5Hz, 2H), 2.70 (dt, J=9.9, 8.1Hz, 2H).

[0119] The third step is to synthesize C8 from C7. In a single-necked flask, add C7 (1.06g, 2.87mmol) and anhydrous stannous chloride (2.73g, 14.4mmol), dissolve in 50mL of anhydrous ethanol, drop 1.0mL of concentrated hydrochloric acid, add a small amount of cuprous chloride to inhibit polymerization, put in a magnetic bar for stirring, and react at 65°C for 1.5 hours. After the reaction is completed, the solvent is removed by rotary evaporation, deionized water is added, and then dichloromethane is added to extract to obtain an organic phase, which is washed with water twice. The organic phase is dried with anhydrous magnesium sulfate, and after drying, the filtrate is collected by filtration, and the solvent is removed by rotary evaporation to obtain the product C8 (0.73g, 2.15mmol), a brown viscous body with a yield of 74.9%, which is directly used for the next step reaction.

[0120] Compound A5 was synthesized from C8. In a single-necked flask, C8 (0.89 g, 2.6 mmol) was weighed, 15 mL of acetone was added, 5 mL of deionized water was added dropwise, 1.50 mL of concentrated hydrochloric acid was added dropwise, and a magnetic stirrer was placed to dissolve it. The mixture was placed at -2°C, sodium nitrite (0.73 g) was weighed and prepared into 5 mL of aqueous solution, and slowly added dropwise to the above solution. After the addition was completed, stirring was continued for 2 hours to obtain a diazonium salt solution, which was recorded as solution 1. In another single-necked flask, 2-naphthol (0.46 g, 3.2 mmol) was accurately weighed, 25 mL of deionized water and 0.15 g of sodium hydroxide were added, the mixture was placed at -5°C, and a magnetic stirrer was placed to completely dissolve it, which was recorded as solution 2. The obtained solution 1 was transferred to a constant pressure dropping funnel, and slowly added dropwise to solution 2. After the addition was completed, stirring was continued for 3 hours, and the color of the solution gradually became darker. After the reaction was completed, acetone was removed by rotary evaporation, an appropriate amount of water was added, and dichloromethane was used for extraction three times. The organic phase was collected and dichloromethane was removed by rotary evaporation. The remaining material was purified by column chromatography (ethyl acetate / petroleum ether=1 / 2) to obtain compound A5 (0.28 g, 0.57 mmol) as a dark red solid with a yield of 21.9%. 1HNMR test was performed on it, 1H NMR (600MHz, CDCl3) δ8.58(t,J=6.9Hz,1H),7.78(t,J=8.9Hz,1H),7.74(t,J=11 .3Hz,1H),7.72–7.56(m,5H),7.40(dd,J=16.7,8.5Hz,6H),6.47(dd,J=17.3,1.2 Hz,1H),6.19(ddd,J=15.8,10.5,5.3Hz,1H),6.11(dt,J=6.2,4.2Hz,1H),5.92– 5.86(m,1H),4.45–4.39(m,2H),3.04(dd,J=14.9,7.2Hz,2H),2.75–2.64(m,2H).

[0121] Example 6

[0122] Synthesis of Compound A6: First, the intermediate C10 was synthesized according to the following synthetic route, and then the compound A6 was synthesized from the intermediate C10.

[0123]

[0124] First, the intermediate C10 was synthesized, which included the following three steps:

[0125] In the first step, C6 is synthesized from m-nitrophenylpropionic acid, and the operation is consistent with that in Example 5.

[0126] In the second step, C9 is synthesized from C6. In a single-necked flask, C6 (5.64 g, 17.9 mmol), triethylamine (2.72 g, 26.9 mmol), and DMAP (0.2 g) are accurately weighed and added thereto, and then 150 mL of tetrahydrofuran is added, and a magnetic bar is placed, and stirred under an ice bath. Then methacryloyl chloride (2.81 g, 26.9 mmol) is weighed, diluted with an appropriate amount of tetrahydrofuran, and slowly added dropwise into the above system in a constant pressure dropping funnel. After the addition is completed, continue stirring for 2 hours, then transfer it to room temperature and continue stirring overnight. Remove the filter residue by suction filtration, collect the filtrate, remove the solvent by rotary evaporation, dissolve the residue in ethyl acetate, wash it three times with saturated sodium bicarbonate and deionized water respectively, collect the organic phase with a separatory funnel, dry the organic phase with anhydrous magnesium sulfate for 4 hours, and collect the filtrate by filtration. The filtrate was evaporated to remove the solvent, and the crude product was collected and purified by column chromatography (ethyl acetate / petroleum ether=1 / 5) to obtain 3.00 g, 7.8 mmol of compound C9 as a colorless viscous liquid. The yield was 43.8%. 1H NMR test was performed to confirm its structure, 1H NMR (600MHz, CDCl3) δ8.12-8.05 (m, 2H), 7.55-7.51 (m, 1H), 7.50-7.44 (m, 1H), 7.39 (d, J = 4.5Hz, 2H), 7.35 (ddd, J = 12.7, 6.8, 3.3Hz, 3H), 6.24-6.18 (m, 1H), 6.14-6.07 (m, 1H), 5.68-5.55 (m, 1H), 4.43-4.35 (m, 2H), 3.09-3.02 (m, 2H), 2.78-2.66 (m, 2H), 2.04-1.95 (m, 3H).

[0127] The third step is to synthesize C10 from C9. In a single-necked flask, C9 (3.00 g, 7.8 mmoll) and anhydrous stannous chloride (7.44 g, 39.2 mmol) were added, dissolved in 150 mL of anhydrous ethanol, 0.4 mL of concentrated hydrochloric acid was added dropwise, a small amount of cuprous chloride was added to inhibit polymerization, a magnetic bar was placed for stirring, and the reaction was carried out at 65°C for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation, deionized water was added, and then dichloromethane was added to extract to obtain an organic phase, which was washed with water twice. The organic phase was dried with anhydrous magnesium sulfate, and after drying, the filtrate was collected by filtration, and the solvent was removed by rotary evaporation to obtain the product C10 (1.96 g, 5.6 mmol), a light yellow viscous body with a yield of 71.8%, which was directly used for the next step reaction.

[0128] Secondly, compound A6 was synthesized from C10. In a single-mouth flask, C10 (0.65 g, 1.9 mmol) was weighed, 15 mL of acetone was added, 5 mL of deionized water was added dropwise, 0.70 mL of concentrated hydrochloric acid was added dropwise, and a magnetic stirrer was placed to dissolve it. The mixture was placed at -2°C, sodium nitrite (0.14 g, 2.1 mmol) was weighed and prepared into 5 mL of aqueous solution, and the mixture was slowly added dropwise to the above solution. After the addition was completed, stirring was continued for 2 hours to obtain a diazonium salt solution, which was recorded as solution 1. In another single-mouth flask, 3-methyl-1-p-tolyl-5-pyrazolone (0.39 g, 2.1 mmol) was accurately weighed, 25 mL of deionized water and 0.082 g of sodium hydroxide were added, the mixture was placed at -5°C, and a magnetic stirrer was placed to completely dissolve it, which was recorded as solution 2. The obtained solution 1 was transferred to a constant pressure dropping funnel and slowly added dropwise to solution 2. After the addition was completed, stirring was continued for 3 hours, and the color of the solution gradually became darker. After the reaction was completed, acetone was removed by rotary evaporation, an appropriate amount of water was added, and the mixture was extracted three times with dichloromethane. The organic phase was collected and dichloromethane was removed by rotary evaporation. The remaining material was purified by column chromatography (ethyl acetate / petroleum ether = 1 / 5) to obtain compound A6 (0.67 g, 1.2 mmol) as an orange-yellow viscous substance with a yield of 63.2%. 1H NMR test was performed to confirm its structure, 1H NMR (600MHz, CDCl3) δ7.84 (d, J=8.4Hz, 2H), 7.47-7.31 (m, 8H), 7.26 (d, J=8.3Hz, 3H), 6.27-6.15 (m, 1H), 6.11-6.06 (m, 1H), 5.66-5.56 (m, 1H), 4.52-4.35 (m, 2H), 3.00 (dt, J=21.2, 7.7Hz, 2H), 2.80-2.65 (m, 2H), 2.39 (d, J=1.0Hz, 6H), 2.04-1.95 (m, 3H).

[0129] Example 7

[0130] Synthesis of Compound A7. First, C10 was synthesized, and then Compound A7 was synthesized from C10. The synthesis operation was the same as that in Example 6. The difference from Example 6 was that in the last step, the raw material for preparing Solution 2 was replaced with p-hydroxybiphenyl (0.48 g, 2.81 mmol), and 15 mL of deionized water and 0.11 g of sodium hydroxide were added. After the reaction was completed, Compound A7 (0.54 g, 1.01 mmol) was obtained by purification as a brownish yellow solid with a yield of 53.2%. 1H NMR test was carried out to confirm its chemical structure, 1H NMR (600 MHz, CDCl3) δ12.93 (s, 1H), 8.24 (dd, J = 5.7, 2.3 Hz, 1H), 7.69-7.64 (m, 3H), 7.47-7.41 (m, 7H), 7.37-7.32 (m, 6H), 6.26-6.12 (m, 1H), 6.12-6.07 (m, 1H), 5.60 (dd, J = 34.2, 1.5 Hz, 1H), 4.55-4.38 (m, 2H), 3.11-3.04 (m, 2H), 2.83-2.73 (m, 2H), 1.95 (d, J = 34.5 Hz, 3H).

[0131] 2. Application test of pigment compounds

[0132] The pigments of Examples 1-7 are used to prepare typical optical materials and test their effects. High oxygen permeability corneal contact lenses often use polymer materials with high fluorine and silicon content as processing masterbatches, while intraocular lenses can use hydrogel materials as processing masterbatches. The use of the pigments in the above two typical formulas to make materials for testing has good representativeness. The pigments are used in the preparation of these two polymers and the production of thin sheet material tests, including Examples 8 to 21. Specifically, in Examples 8 to 14, a hard corneal contact lens formula with a Dk value of about 100 is selected to copolymerize with the pigment compound, and the comparative examples are respectively adding two commonly used commercial inactive pigments (Comparative Examples 1 and 2) and preparing materials without adding pigments (Comparative Example 3). In addition, in Examples 15 to 21, a hydrophilic intraocular lens formula is selected to copolymerize with the pigment compound, and the comparative example does not add pigment to prepare a colorless material (Comparative Example 4).

[0133] Embodiments 8 to 14

[0134] The pigment compound A1 in Example 1 was added to prepare a colored sheet material for corneal contact lenses. 54.44% of hexafluoroisopropyl methacrylate, 24.75% of methacryloyloxypropyl tris(trimethylsiloxy)silane, 5.94% of methacrylic acid, 6.93% of neopentyl glycol dimethacrylate, 6.93% of dimethacryloyloxypropyl polymethylsiloxane, 0.50% of 2,5-dimethyl-2,5-bis(2-ethylhexanoic acid peroxy)hexane, 0.50% of 2-hydroxy-4-(methacryloyloxy)benzophenone, and 0.018% of pigment A1 were accurately weighed in a single-necked flask and uniformly mixed by ultrasonication. Take another polypropylene mold, add the fully miscible stock solution after filtering, seal the mold, put it into an oven, cure at 50°C for 5 hours, then raise the temperature to 70°C for 20 hours, remove from the mold after curing to obtain a cylindrical material, and the cylindrical material is mechanically processed to obtain a sheet material with a smooth surface and a certain thickness, which is recorded as D1. D1 is used for subsequent tests, and this preparation experiment is recorded as Example 8. Under the same operation, pigments A2 to A7 are selected to replace pigment A1 to prepare the material, and the remaining sheet materials are obtained, which are recorded as D2 to D7, and the preparation experiments are recorded as Examples 9 to 14.

[0135] Examples 15 to 21

[0136] The pigment compound A1 in Example 1 is added to prepare a colored intraocular lens sheet material. Accurately weigh 83.2% of hydroxyethyl methacrylate, 16.8% of methyl methacrylate, 1.02% of ethylene glycol dimethacrylate, 0.03% of azobisisobutyronitrile, 0.82% of 2-(4-benzoyl-3-hydroxyphenoxy)ethyl acrylate, and 0.020% of pigment A1 in a single-necked flask and mix them evenly by ultrasonication. Take another polypropylene mold, filter the completely miscible stock solution and add it to the mold, seal the mold, put it in an oven, cure it at 50°C for 2 hours, then increase the temperature to 70°C and cure it for 10 hours. After curing, remove it from the mold to obtain a circular buckle sheet material. The buckle sheet material is mechanically processed to obtain a thin sheet material with a smooth surface and a certain thickness, which is recorded as E1. It is used for subsequent tests, and the preparation experiment is recorded as Example 15. Under the same operation, pigments A2 to A7 were selected to replace pigment A1 to prepare the materials, and the remaining flake materials were obtained, which were respectively recorded as E2 to E7, and the preparation experiments were respectively recorded as Examples 16 to 21.

[0137] Comparative Examples 1 and 2

[0138] Adding commonly used inactive pigments to prepare corneal contact lens sheet materials. According to the material ratio of Example 8, two mature commercial inactive pigments, 1,4-bis(p-tolylamino)anthracene-9,10-dione and 4-[(2,4-dimethylphenyl)azo]-2,4-dihydro-5-methyl-2-phenyl-3H-pyrazol-3-one, were used to replace pigment A1, and copolymer sheet materials for comparison were prepared under the same operation, which were respectively recorded as D8 and D9, and the preparation experiments were respectively recorded as Comparative Examples 1 and Comparative Examples 2.

[0139] Comparative Example 3

[0140] A colorless corneal contact lens sheet material was prepared without adding pigment. According to the material proportions of Example 8, but without adding pigment, a sheet material was prepared under the same operation, which was recorded as D10.

[0141] Comparative Example 4

[0142] Preparation of colorless intraocular lens sheet material without adding pigments According to the material proportions of Example 15, but without adding pigments, a colorless sheet material was prepared under the same operation, which was recorded as E8.

[0143] 3. Optical performance test

[0144] 1. Determination of the spectral absorption curve of the pigment: For the solution, the substance to be tested was dissolved in ethyl acetate to prepare a solution of a certain mass concentration, and the concentration of the solution was recorded. In a specific quartz cell, a Shimadzu visible-ultraviolet spectrophotometer, model UV-1900i, was used to measure its spectral absorption curve in the wavelength range of 200 to 800 nm.

[0145] 2. Determination of pigment molar absorption coefficient: Dissolve a certain mass of substance in ethyl acetate, record its molar concentration c, and determine the maximum absorption wavelength λ max The molar absorption coefficient at . Calculation formula: molar absorption coefficient ε = A / cl, where A is the absorbance and l is the optical path length of the quartz cell.

[0146] 3. Determination of the spectral absorption curve of copolymer optical materials: Prepare sheet materials and grind and polish them into a smooth surface with a thickness of 1.0 mm. Use Shimadzu visible-ultraviolet spectrophotometer, model UV-1900i, to measure the spectral absorption curve within a specific wavelength range.

[0147] 4. Determination of color coordinates of copolymer optical materials: Prepare sheet materials and grind and polish them into a smooth surface. Use a colorimeter Datacolor 400, use a D65 light source, and a viewing angle of 10° to measure their color coordinates (L, a, b).

[0148] 5. Determination of the spectral transmittance curve of the copolymer optical material: a sheet material was prepared and polished to a smooth surface, and its spectral transmittance curve in the wavelength range of 300 to 1100 nm was measured using a Shimadzu visible-ultraviolet spectrophotometer, model UV-1900i.

[0149] 6. Pigment elution test method for copolymer optical materials: prepare thin sheets of material with the same thickness, soak them in 5 ml of anhydrous ethanol, seal them strictly, and place them in an air bath oscillator at 55°C for 5 hours. After the shaking, take out the sheet, rinse the surface of the sheet with fresh ethanol and water in turn, and then put them in a vacuum drying oven and dry them at 45°C for 3 hours.

[0150] 4. Test result representation

[0151] 1. Characterization of Pigments

[0152] Figure 1 The absorption spectrum curves of pigments A1 to A7 in the range of 300 to 800 nm measured according to the above method. Due to the different molecular structures that affect the effect of substances on light, the main absorption spectra and absorption capacity of the different pigment compounds synthesized in this application show different spectral characteristics. The spectral absorption in the wavelength range of 300 to 800 nm is as follows: Figure 1 In response to the specific needs of optical materials, these spectral differences provide more screening ranges for preparing materials with suitable optical characteristics, such as pigments with suitable color coordinates, blue light absorbers with suitable shielding ranges, etc. Pigment-related parameters are calculated and recorded in Table 1 below based on the original data.

[0153] Table 1

[0154]

[0155]

[0156] 2. Characterization of performance for making corneal contact lenses

[0157] Ten types of corneal contact lens sheets, D1 to D10, were prepared. Figure 2 As shown. In order to quantitatively characterize the color of the material, the color coordinates were measured, and the results are shown in Table 2. The color meaning represented by the color coordinate value is consistent with the real object. The difference in the molecular structure of the pigment brings about the difference in the color coordinates, that is, within a certain color coordinate range, the pigment of the present application can better achieve the function of fine color adjustment by changing the structure. The following Table 2 shows the color coordinates (L, a, b) and color of corneal contact lens materials D1 to D10.

[0158] Table 2

[0159] Preparation test Contact lens materials Color coordinates (L, a, b) Color coordinates color meaning Example 8 D1 (96,-11,33) Green and yellow Example 9 D2 (96,-13,49) Green and yellow Example 10 D3 (96,-2,14) Green and yellow Embodiment 11 D4 (96,-13,49) Green and yellow Example 12 D5 (87,19,40) Red and yellow Embodiment 13 D6 (96,-11,34) Green and yellow Embodiment 14 D7 (97,-5,17) Green and yellow Comparative Example 1 D8 (72,-32,-21) Green Blue Comparative Example 2 D9 (94,-14,77) Green and yellow Comparative Example 3 D10 (98,0,1) colorless

[0160] 3. Characterization of performance for making intraocular lenses

[0161] Pigments are used in the preparation of intraocular lens materials E1 to E8, and their spectral transmittance is as follows Figure 3 As shown. The blue light absorption is calculated based on the measured original data of spectral transmittance, and the results are shown in Table 3. As can be seen from the table, the transmittance of materials with different pigments in the blue light region (400-500nm) shows a large difference, and there is no differentiated absorption in the visible light spectrum outside the blue light region. These differentiated characteristics of spectral absorption in specific regions are the basis for precise control of the material spectrum. That is, for the pigments of the present application, the spectral absorption of the material can be controlled by selecting pigments with suitable structures and suitable concentrations. Therefore, the pigments of the present application can meet the customized adjustment of blue light absorption of intraocular lens materials, and can be used as a good blue light absorber for intraocular lenses. Table 3 below shows the spectral transmittance parameters of intraocular lens materials E1-E8 in different spectral bands.

[0162] Table 3

[0163]

[0164] 4. Investigate the migration of pigments to the mold

[0165] On the one hand, the migration and precipitation of pigments during the material preparation process were investigated. The state of pigment staining in the mold after curing of materials D1 to D10 was observed. The outward migration of pigments can be seen from the staining state of the mold after curing. As in Examples 8 to 14 and Comparative Examples 1 to 2, polypropylene molds were used to prepare colored materials D1 to D7 and D8 to D9 respectively. Comparative Example 3 did not add any pigment and prepared colorless material D10 as a blank control. After curing, the mold staining was checked. Figure 4 As shown, Figure 4 From left to right in the figure are the molds after curing of materials D1 to D10. From the appearance, it can be seen that the materials prepared with the active pigments of the present application (D1 to D7) did not have the problem of pigment staining the mold, that is, the synthetic pigments of the present application were firmly bound inside the material during the curing process, while the materials prepared with inactive pigments (D8 to D9) left obvious pigment marks on the mold wall (that is, the situation of obvious pigment staining the mold occurred), that is, the inactive pigments in the control group migrated significantly outward during the curing process. Therefore, the materials prepared with the participation of the pigments of the present application have better dyeing non-migration and safety.

[0166] On the other hand, the material's pigment resistance and stability are tested.

[0167] First, the material pigment elution is directly verified. In the test, several corneal contact lens sheet materials D2, D3, D5, D8, D9, and D10 are randomly selected for immersion elution verification according to test method 6. Figure 5 The substance in the middle is the soaking and washing liquid of the thin sheet material, from Figure 5 It can be seen that after soaking and eluting, the extracts of the materials D2, D3, and D5 of the embodiment group and the extracts of the blank comparison group material D10 without pigment are all colorless, while the extracts of the materials D8 and D9 of the comparative example group have obvious pigment dissolved in. In order to further confirm the dissolution of pigment in the extract, the spectral absorption of the extract can be tested. The characteristic absorption of the pigment is between 350 and 700nm. The test results show that compared with the comparison groups D8 and D9, the extracts of the materials D2, D3, and D5 of the embodiment group absorb very weakly in this range, which is similar to the blank comparison sample D10 without pigment addition, while the comparative examples D8 and D9 have large absorption peaks in this range. The above tests prove that the materials prepared by the pigment of this application have good pigment anti-elution characteristics.

[0168] At the same time, the color coordinates of the thin slice samples D2, D3, D5, D8, D9, and D10 after the above leaching and elution can be tested again, and the color coordinate changes before and after elution are calculated to evaluate their color retention ability. The results are shown in Table 4 below. Compared with before immersion and elution (data in Table 2), after immersion and elution, the color coordinates of the embodiment groups D2, D3, D5, and the blank control group D10 did not change much, that is, the original color was well maintained, while the color coordinates of the comparative groups D8 and D9 changed greatly, and significant fading occurred. This also further proves that the pigment preparation material of the present application has a good pigment anti-elution ability.

[0169] Table 4

[0170]

[0171] Then verify the changes in the material spectra before and after elution. In order to compare the changes in the material spectra before and after elution, several materials E4, D5, D8, and D9 can be selected for comparison before and after elution. The results are as follows: Figure 6 , 7 , 8, and 9, Figure 6 is the spectral transmittance curve of intraocular lens material E4 before and after leaching and elution. Figure 7 This is the spectral transmittance curve of corneal contact lens material D5 before and after leaching and elution. Figure 8 This is the spectral transmittance curve of corneal contact lens material D8 before and after leaching and elution. Fig. 9The spectral transmittance curve of the corneal contact lens material D9 before and after leaching and elution. From the transmittance change of the characteristic absorption section, it can be seen that in the embodiment, the spectral transmittance of the intraocular lens material E4 and the corneal contact lens material D5 changes very little, while the spectral transmittance of the comparative corneal contact lens materials D8 and D9 changes greatly. This also shows that the pigment of the present application is resistant to elution and has good stable coloring ability.

[0172] Through the above verification tests, it can be considered that the pigment of the present application has good pigment anti-washing ability and color stability when used in the preparation of polymer optical materials.

[0173] The serial numbers of the above-mentioned embodiments of the present application are for description only and do not represent the advantages or disadvantages of the embodiments.

[0174] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A pigment compound, characterized in that The pigment compound has a structure shown in the following formula (I): Wherein, A is a hydrogen atom or a methyl group; R1 is a hydrogen atom, a halogen atom, a cyano group, an aryl group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and n=1, 2, 3, 4 or 5; k = 0, 1, 2, 3, 4, 5 or 6; R2 is a hydrogen atom, a halogen atom, a cyano group, a nitro group, a sulfonic acid group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and m=1, 2, 3 or 4; B is a cyclic conjugated group, a derivative of a cyclic conjugated group, or a substituted derivative of a cyclic conjugated group.

2. The pigment compound according to claim 1, characterized in that The B has a structure as shown in the following formula b1: wherein R3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group; R4 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

3. The pigment compound according to claim 2, characterized in that It has a structure shown in the following formula A1, A2 or A6:

4. The pigment compound according to claim 1, characterized in that The B has a structure shown in the following formula b2: wherein R3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group; R4 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group.

5. The pigment compound according to claim 4, characterized in that It has the structure shown in the following formula A4:

6. The pigment compound according to claim 1, characterized in that The B has a structure shown in the following formula b3: wherein R3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group; i=1, 2, 3, 4 or 5.

7. The pigment compound according to claim 6, characterized in that It has a structure shown in the following formula A3 or A7:

8. The pigment compound according to claim 1, characterized in that The B has a structure shown in the following formula b4: wherein R3 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group; R4 is a hydrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, a cyano group, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an aryl group having 6 to 12 carbon atoms, a halogenated alkyl group having 1 to 6 carbon atoms, a halogenated alkoxy group having 1 to 6 carbon atoms, a halogenated aryl group having 6 to 12 carbon atoms, a hydroxyl group, an amino group, or an alkyl-substituted amino group; i = 1, 2 or 3; j=1, 2, 3 or 4.

9. The pigment compound according to claim 8, characterized in that It has the structure shown in the following formula A5:

10. An optical material, characterized in that: The pigment compound comprises the pigment compound as claimed in any one of claims 1 to 9, wherein the pigment compound forms a covalent bond with an olefin monomer through copolymerization.